PELAKSANAAN KESEHATAN LINGKUNGAN DAN PENGENALAN MANAJEMEN BISNIS SYARIAH DI DESA SUKAMAJU, KECAMATAN CIBUNGBULANG, KABUPATEN BOGOR - Fitria Setia Rahman; Rully Trihantana; Ermi Suryani (Jurnal Pengabdian Kepada Masyarakat Manajemen Bisnis Syariah: Program Studi Manajemen Bisnis Syariah, 2021)
Abstract Covid-19 is a pandemic that occurs in various parts of the world and is a form of public concern. Transmission of this disease can be prevented by maintaining cleanliness, one of which can use antiseptics and disinfectants. This study aims to demonstrate the effectiveness of the use of antiseptics and disinfectants to prevent the transmission of Covid-19 in the Sukamaju village community. It can be concluded that the use of antiseptics and disinfectants to prevent the transmission of Covid-19 is effective if the selection is right and is used according to its designation. There is a need for further education by health workers to the public in order to be a preventive measure against the further spread of Covid-19. When the status of the Covid-19 pandemic was declared, various countries made efforts to prevent the transmission of the disease; Indonesia is no exception. One way to break the chain of transmission is to carry out disinfection. This article is a scoping review with the aim of getting an overview of the implementation of disinfection in preventing the transmission of Covid-19 in public areas and the possible health risks posed. The method of collecting data/information is by searching the websites of various ministries/agencies and online media within a period of 3 (three) months, starting from March 2020 (determination of the Covid-19 pandemic) until May 2020. The data and information collected includes references, locations, methods , the target of disinfection, as well as the disinfectant used, and its effect on health. Data analysis was done descriptively. The results show that disinfection in public areas, in offices, health facilities (hospitals and health centers), housing, shopping centers/malls/markets, and transportation areas (roads, terminals, bus stops, and vehicles) is carried out by spraying directly on the surface /objects that are frequently touched and in the disinfection booth, use a disinfectant that is irritating. The implementation of disinfection in several public areas is still not in accordance with the Disinfection Protocol/Guidelines in the Prevention of Covid-19 Transmission, so that it has the potential to pose a health risk. It can be concluded that the implementation of disinfection in public areas has the potential to pose a health risk. There is a need for supervision in the implementation of disinfection and socialization as well as education about potential health risks to the community. Keywords: Covid-19, Disinfection Protocol/Guidelines, education about Shariah Business Management to the community.